Performance analysis of a modified solar array under shadow conditions - Sharma A.K.; Dwivedi R.; Srivastava S.K.; Pathak C.M. (My University, 2025)
This paper deals with the performance studies of a photovoltaic panel under shadow conditions. The conventional solar array design approach has been modified using a bypass diode across each cell, and the performance of the modified panel has been evaluated experimentally. The observed experimental results have been compared to those obtained theoretically, taking account of the effect of additional series resistance due to the shadowed area. Excellent agreement, both qualitatively and quantitatively, between experiment and theory has been obtained. © 1994.